Natural Radioactivity in Groundwater in Phra Nakhon Si Ayutthaya Province - Kodcharin, Paradee; Youngchuay, Udorn; Chinwetkitvanich, Sopa (Applied Environmental Research, 2018)
This research aims to study the specific activity of natural radioactivity in groundwater samples taken in the area of Phra Nakhon Si Ayutthaya Province, Thailand. Totally, sixty groundwater samples collected from wells in eight districts were monitored and determined for radionuclides 226Ra, 232Th and 40K and gross alpha and beta were determined using high resolution gamma spectrometer and Canberra Tennelec Series 5 gas flow proportional counter, respectively. Most of the sixty wells serve for water consumption and some other wells for agricultural. The results showed that the average activity concentrations of the gross alpha and beta were 0.01±0.007 and 0.15±0.02 Bq L-1 and the specific activity of 226Ra, 232Th and 40K were averagely 0.77±0.13, 1.03±0.19 and 15.56±1.28 Bq L-1, and respectively. The activity concentrations of the gross alpha and beta and the specific activity of the radionuclides in these samples exhibited quite low as compared to the recommended reference level for human consumption reported by World Health Organization (WHO).